Measuring student learning outcomes on Outward Bound courses and associated independent variables - Foley, Jeffrey M., author; Kaminski, Karen, advisor (Colorado State University. Libraries, 2009)
Outward Bound in the United States takes over 20,000 students a year into unique environments and challenges them to develop their character, leadership, and service ethic. Past research has shown an increase in students' self-confidence, leadership, self-esteem, self-efficacy, interpersonal skills, intrapersonal skills, and other skill types. This study conducted a pre-exposure, post-exposure, and follow-up quasi-experimental design that demonstrates that most of Outward Bound's learning outcomes currently stated in the organization's educational framework were met. The experimental group showed statistically significant increases to character development (p < .001, η2 = .146), leadership development (p < .001, η2 = .837), and service development (p < .001, η2 = .175) from pre-exposure to post-exposure surveys. These gains were not maintained over time. Twelve sub-variables (self-confidence, self-actualization, compassion towards others, healthy/balanced life, goal setting, group collaboration, effective communication, conflict resolution, problem solving, social responsibility, environmental responsibility, and service to others) were also analyzed with all but one showing statistically significant positive change from pre-exposure survey to post-exposure survey. Few of these changes were maintained to the follow-up survey. The independent variables of course characteristics (course length and type), instructor demographics (age, education, tenure, training), and student demographics (age, gender, ethnicity) were analyzed. The independent variables of course characteristics, instructor demographics, and student demographics did not have an effect on students achieving stated learning outcomes. Overall, students on an Outward Bound course (p < .001, η2 = .191) experience a significant positive change in character, leadership, and service, but these changes were not maintained over time.
Keywords: experiential education; experiential learning; experiential learning assessment; outdoor education; outward bound; community college education; curriculum development; variables